Plataformização do trabalho e desigualdade social: reflexões a partir da categoria dimensão subjetiva da realidade - Carvalho, Mônica Gurjão (2024)
In the context of the productive restructuring of capital, the world of work has undergone several transformations, in light of which digital platforms are already a reality and their interference and influence require our reflection. If at first glance platforms appear to be exclusively technological means, it should be noted that they are influenced by public and private structures that operate in different fields of everyday life (food, transport, health, relationships, etc.). The platformization of work is a complex phenomenon that goes beyond the use of applications and platforms, since these are just the visible interface of a software, a program installed on a computer or cell phone, a field of interaction of a system which is economic, social, political and technological, with multiple repercussions. Faced with this scenario, the challenge is to recognize that, if, on the one hand, platforms and applications already present themselves as undeniable work structures, we cannot mystify them by allowing the social processes involved to be hidden. By not mystifying this phenomenon, we can recognize that it has meant the exploitation and subordination of a range of workers who start to be used by large corporations that use applications to obtain profit by exploiting popular layers more prone to exclusion and social marginalization – women, black people and young peripheral people – individuals who historically, in Brazil, have always faced the harshest face of capitalism and continue to be subordinated and exploited through this type of work. This research aimed to understand the subjective dimension of work platformization. The subjective dimension of reality category gives visibility to the presence of subjects in the construction of reality, providing the opportunity to understand that social phenomena have a dimension of images, values, ideas, affections, etc., which is complex, dialectical, contradictory. We take this category and the theoretical-methodological basis of socio-historical psychology to think about the overlaps between the platformization of work and social inequality, also relating these aspects to the subordinate and dependent capitalism that has been installed in Brazil since the colonial period. Theory and method for socio-historical psychology are inseparable and are based on Marxist epistemology. Therefore, these are not just tools, instruments to be used to understand reality; it involves an understanding of the world, of human beings and a conception of knowledge. The phenomenon of inequality is complex and intrinsic to the capitalist mode of production. In the Brazilian case, social inequality is linked to connections of race, class and gender, imposing injustices and the absence of social rights for the vast majority of the population. This research included five semi-structured interviews with different workers who work in the field of platformed work. We seek to overcome the meritocratic-neoliberal discourse, highlighting how ideological explanations camouflage the social and historical production of inequality present, especially in the platformed labor market. As a result, we found that the logic of the platformization of work extends beyond the phenomenon of work, becoming a practice of mediating life today, which contributes to the maintenance of a series of oppressions already present in Brazil since the colonial period, especially the racism. Finally, we highlight that the platformization of work has accelerated, through the use of technology, the weakening of labor relations and the denial of the centrality of work as a founding element of the human and essential to the fight against social inequality, making legislative measures urgent on the subject